Keberagaman Tradisi Perkawinan Masyarakat Suku Kajang dalam Perspektif Filsafat Hukum - Irwandi; Yusuf Setyadi (Universitas Ngudi Waluyo, 2023)
This journal aims to explain the law on marriages for the Kajang people in South Sulawesi, to be precise in Bulukumba Regency, customary law for marriages for the Kajang people, and the prohibition on marriages between the Kajang people and other tribes. The conclusion of this journal is that there is legal pluralism in tribal marriages, namely customary law, religious (Islamic) law, and positive law. However, the interesting thing is that they prioritize customary law in their marriage procession. And those who violate it will be subject to customary sanctions, namely being expelled from the customary area of the Kajang tribal area. Abstrak Jurnal ini bertujuan untuk menjelaskan tentang hukum dalam perkawinan masyarakat suku kajang di Sulawesi Selatan tepatnya di Kabupaten Bulukumba, hukum adat pada perkawinan masyarakat suku kajang, dan larangan perkawinan masyarakat suku kajang dengan suku lainnya. Kesimpulan pada jurnal ini adalah, terdapat pluralism hukum pada perkawinan masyarakat suku kajng yakni hukum adat, hukum agama (islam), dan hukum positif. Namun menriknya mereka lebih mengutamakan hukum adat dalam prosesi perkawinannya. Dan yang melanggar akan dikenakan sangsi adat yakni dikeluarkan dari kawasan adat wilayah suku kajang.